STUDENT LEADERSHIP IN PUBLIC UNIVERSITIES IN KENYAN - Kithuri, Fr. Dr. Kinoti E.; Thuranira, Prof. Simon (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The study investigated modern university and college leadership / governance, illuminates on students’ leaderocomics across the world with specific Kenya’s high education private and public universities leadership experience as leaders and/or the lead and presence of any leadership training modeling to the university students. Student leadership or leadership by young people has always existed in school and community settings. While there are many programs devoted to leadership development and training, this study, focused on what young people conceive leadership to be and in what circumstances the students have experienced leadership. The components of experience of leaderships range from legal framework of university leadership. The composition of those who take up leadership in terms of gender, year of study and class level, tribal affiliation, coalition formation strategies in high education leadership. The study looked into the predicted consequent to the large national leadership trajectory. In addition, the study looked at leadership functions, perception and challenges as well recommendations for improvement. Kenyan Universities, both public and private have the same structure of students’ leadership as guided by University Act of 2012. Student leadership in universities in Kenya is a microcosm of the national politics in the country. The study framing the review in authentic and servant, transformative leadership, integrated with best practices in learning and training. Methodology -The study followed a “systematic review", "narrative review", "meta-syntheses’ design. The Objective was assessing the Student Leadership, any relationship between type of leadership and students’ wellbeing in high education. Sample -The population targeted was students in college and university. The study’s sample articles writing between 2015- 2024. The articles samples were obtained through online library Google scholar, ScienceDirect, Pubmed, Education Resources Information Center (ERIC), and specifically on leadership; seismic articles which include; Forbes, Fast Company, Harvard Business, and Huffington Post. The study reviewed articles utilizing specific instruments with psychometric properties of the student’s leadership; Student Leadership Practices, Cronbach alpha coefficients (69 to .80) Observer version (0.82.) The Servant Leadership Scale (SL-28) (Liden et al., 2008), reliability coefficients (0.82 to 0.92) and transformational leadership (MLQ) (0.94 (94 %). Since Cronbach's alpha coefficient more than 70% is acceptable. Conclusion; Each of these instruments report Modest to strong internal reliability coefficients There is well representation of gender in students’ leadership, the consistency of exposure to leadership to students from early age is recommended. An increase of exposure of students to leadership training mentors is gap that needs to be bridged and opportunities expanded from early age.